Financial Literacy of Teachers in Selected Private Schools - Del Rosario, Editha (International Journal of Sustainability and Advanced Integrated Research, 2026)
Financial literacy among private school teachers plays a crucial role in ensuring effective personal financial management and long-term economic security. This study examined the financial literacy of teachers in selected private schools in Binangonan, Rizal during School Year 2025–2026. Using a descriptive survey research design, data were gathered from 103 private school teachers through a researcher-made questionnaire covering retirement planning, budgeting and saving, insurance, and investing. Respondents were profiled in terms of age, sex, civil status, position title, educational attainment, length of service, and in-service training attended. Findings show that most respondents were young adults aged 20–25, predominantly female, single, contractual, and with 0–5 years of service, holding baccalaureate degrees and attending school-level trainings. Inferential results using F-test revealed that demographic and professional variables significantly influence financial literacy in selected domains. Age significantly affected retirement planning, budgeting and saving, and investing, while gender influenced only budgeting and saving. Civil status showed no significant differences across all financial literacy areas. Position title affected retirement planning and budgeting, while educational attainment influenced investing. Length of service was significant in retirement planning, insurance, and investing. In-service training significantly improved retirement planning, budgeting and saving, and investing literacy. However, it had no significant effect on insurance literacy. The study concludes that financial literacy among teachers varies depending on demographic and professional characteristics, and targeted interventions are necessary to address gaps. It recommends the integration of structured financial literacy programs, expert-led seminars, incentive-based financial wellness initiatives, and onboarding financial education. Establishing peer support systems and providing continuous access to financial guidance are also encouraged. Future research may explore additional variables to further strengthen understanding of teachers’ financial literacy. These findings provide practical implications for school administrators and policymakers in enhancing teacher financial well-being and institutional support systems in private education sectors in the Philippines context.